Effectiveness of using rituximab in membranous nephropathy: a clinical case - Zavalna, I.M.; Lagodych, Ye.K. (KIDNEYS, 2024)
Membranous nephropathy is a glomerulopathy in which the primary target is the podocyte and damage to the glomerular basement membrane. The disease occurs more often in adults, mostly in people over 50 years old. The clinical manifestation is nephrotic syndrome, but in most cases, asymptomatic proteinuria may develop. In the mechanism of kidney damage, the deposition of immune complexes in the subepithelial space of the capillary loop of the glomerulus with subsequent activation of the complement system is important. Over the past twenty years, great progress has been made in the identification of potential target antigens, the main of which is the M-type phospholipase A2 receptor (PLA2R) protein with circulating anti-PLA2R antibody, which allows for assessment of the activity and prognosis of membranous nephropathy. This path of damage corresponds to approximately 70–80 % of cases of membranous nephropathy, which is characterized as primary.